RISK FACTORS RELATED TO BREAST CANCER DEVELOPMENT - Bastos, Daniel Rodrigues de (Mastology, 2019)
Breast cancer is a disease that affects women worldwide, and therefore is a health problem of global concern. Despite scientific and technological advances in basic researches and in clinical studies, breast cancer still presents numerous obstacles that need to be overcome in order to ensure better survival for patients affected by this disease. Science’s work is not only to predict the best methods of treatment, but also to prevent the onset of symptoms and, consequently, of the tumor. Recent articles discuss numerous factors which may contribute to tumor initiation and progression. They take into consideration social habits, such as smoking, alcohol drinking, diets that contribute to hyperlipidemia or increased availability of antagonist molecules that act on the cell in order to create a favorable microenvironment to tumorigenesis. In addition to that, factors related to family history and hereditary predisposition are important, even though they explain a minimal portion of cases. Thus, the purpose of this article is to address modifiable and non-modifiable risk factors, related to breast cancer progression.